Climate change and non-native species in the Spanish Network of National Parks - Gallardo, Belinda; Capdevila-Argüelles, Laura (Biological invasions, 2024)
The Iberian Peninsula is a primary entry point for non-native species (NNS) into Europe via maritime routes, and is a significant tourist destination. This positions the highly diverse Spanish National Parks at high risk from invasive species, necessitating proactive adaptation and mitigation strategies. We present a comprehensive analysis of the risks posed by NNS to the network of 15 continental and marine National Parks in Spain under climate change, aiming to align management strategies with international Global Biodiversity Framework (GBF) targets. We identified 200 NNS across the network of National Parks, including 78 listed in national NNS regulations. Park managers helped identify 22 priority NNS, including the water hyacinth, American mink, Cape fig and wakame, among others. Over half of the 22 priority NNS (55%) were classified as having a “Major” impact on native biodiversity according to EICAT standards, with another 23% considered “Massive”. Distribution models suggest that rising minimum temperatures could enable NNS to expand in altitude within the parks, particularly in high-mountain parks. Species like the barbary sheep, water hyacinth and largemouth bass may particularly benefit from global warming. Our findings prioritize national parks most vulnerable to the double threat posed by climate change and invasive species, such as Islas Atlánticas, Doñana and Archipelago de Cabrera. We conclude that, in order to progress towards achieving GBF goals, it is essential to: (i) coordinate NNS management efforts across administrations (national and regional), (ii) integrate resources and expertise in a unified strategy against invasion across the network and (iii) enhance public awareness about the risks of introduction and impact of NNS.